La planification, l’exécution et le suivi : trois facteurs importants dans l’atteinte d’objectifs informatiques - Luccisano, Domenic J. (Assurances, 1988)
Computerization is an art in itself. Though computer systems are costly, both in equipment and in maintenance, they do offer quite an extraordinary solution to information problems. No longer can we content ourseIves with a few general details; action must be planned and analyzed to ensure the results expected. This is what a delicate and complex, yet precious resource allows us to achieve when the right solution is found. Our collaborator, Mr. Domenic J. Luccisano, has examined the extensive research which had to be undertaken before reaching a final decision in a particular case, here Dale-Parizeau, both during the installation process and afterwards. The group consists of thirty-five offices across the country. In his article, Mr. Luccisano presents the various studies undertaken to equip the group with efficient facilities, taking into account local needs and the control required for the system as a whole. In this article, the reader will find the solution to these problems which one of our collaborators, Mr. André Parizeau, described in Thoughts on Computer Systems, published in our October 1987 issue.